Estudo da ação dicotômica do receptor de estrógeno beta (ERβ) na indução da transição epitélio- mesênquima em células tumorais de mama da linhagem MCF-7 - Silva, Danielle (2017)
Breast cancer is the most common neoplasm of women in the world. Among the prognostic factors taken into consideration are the hormonal receptors. The estrogen receptor beta (ERβ) is one of the hormone receptors that can be found in the breast, but is not used as a predictive marker of tumor prognosis due to its paradoxical action. Tumor cells of the MCF-7 lineage were used in this work to ascertain the dichotomic function of ERβ in the tumor process. Thus, we evaluated some of the processes that are observed in the stages of breast cancer development, such as proliferation, epithelial-mesenchymal transition (EMT) and cancer stem cell research (CSCs). For this, ERβ agonist Diarilpropionitrile (DPN), ambiguous agonist (ERα and ERβ) estradiol (E2) and transforming growth factor beta (TGF-β), inducer of EMT, were used. Cells receiving TGF- β treatment obtained a higher number of CSCs compared to those that were not cultured with this agonist, a result found by the flow cytometry technique. Cells that were pretreated with TGF-β demonstrated a lower rate of proliferation and increased expression of p21, a protein with cyclin D1 blocking action, whose expression was unchanged in TGF-β and ERβ agonist treatments. Regarding the EMT-related genes (SLUG, SNAIL, VIMENTINA, ZEB1, TWIST1, RBFOX2, CYCLINAD1 and p21), ERβ inhibited their expression, suggesting that this receptor induces the phenomenon called epithelial mesenchymal transition (MET). In this scenario, DPN caused a decrease in the expression of SLUG, SNAIL, TWIST, in contrast to TGF-β expression, which, in addition to these genes, also showed increased expression of ZEB1, RBFOX2 and VIMENTIN. The effect of TGF-β on EMT was reversed by associating it with DPN. The data corroborate with the literature about the possible ERβ pro-tumor role in increasing cell proliferation and the generation of breast cancer stem cells (BSCs), in addition to the MET related phenotype in treatments with DPN alone or associated to TGF-β. With these results, it becomes clear in our work that depending on what is evaluated in relation to the action of ERβ, previously treated or not with TGF-β, its dichotomous effect is still observed.